Islam Perspektif dan Perspektif Islam tentang Pendeta Syaifudin Ibrahim (Analisis Pandangan, Asumsi, dan Tantangan Pendeta Syaifuddin IbrahimTerhadap Umat Muslim) - EKO NOPRIYANSA (Jurnal khabar: Komunikasi dan Penyiaran Islam, 2019)
The series of past history reminds religious people that the Presence of Religion is on the most principle principle, in order to be a solution in various aspects of human life, apart from the dark history of Religion which is ridden by the interests of power and vice versa on the power of Religion. The presence of Christianity as a Missionary religion and Islam as a Da'wah religion opened a space for religious social dialogue, because both were involved in Agamanization. this article exposing the views and assumptions of Reverend Murtadin Saifudin Ibrahim who has an Islamic background and assumes that he is one of the Islamic leaders who then turned to become a Christian priest. this article is not an Interference to Saifudin Ibrahim's new beliefs, but this article is to answer Saifudin Ibrahim's assumptions and views on Islam as the largest religion among religious people in Indonesia.this article can answer various obscure views and thoughts, and thoughts that intercept the faith in Islam in Indonesia.